Assessing the effectiveness of vaccination strategies against respiratory pathogens⁠ - Abdullah, Marwah Y.; Alanazi, Faisal M.; Gandurah, Saad F.; Altufayif, Dhiyaa A.; Alghamdi, Abdulrahman M.; Halawani, Olfa A.; Almudarhem, Fatimah F.; Al-Otaibe, Raghad I.; Allathiqani, Osama M.; Alasmari, Amani A. (International Journal Of Community Medicine And Public Health, 2025)
Vaccination has been an effective method in preventing many childhood-related infections and reducing the risk of infections in adults. Between the mid-1960s and 2015, vaccination has been successful in saving more than 10 million lives. Respiratory pathogens have been a main target for vaccination over decades. Many vaccines were developed against respiratory pathogens such as influenza. virus, Streptococcus pneumoniae, and Mycobacterium tuberculosis. Vaccination against respiratory pathogens faces new challenges every year due to different reasons. The following databases were used in systematic research: Medline (PubMed), Web of Science, and Scopus. Summaries of the found studies were exported by EndNote X8, and duplicate studies were removed. Inclusion criteria were any study. Despite the proven effectiveness of various vaccines against respiratory pathogens, several challenges persist in this field. These include the waning of vaccine-induced immunity, prompting the need of developing vaccines that provide long-lasting protection; vaccination harmful side effects; and the emergence of new subtypes are examples of these challenges. In the aftermath of the COVID-19 pandemic, clinical trials are underway to develop more effective vaccines against a range of pathogens. However, greater large-scale efforts are needed, particularly in low-income countries, to enhance global public health outcomes.